Patient Pill Organization Strategies and Adherence Measured in a Cross-Sectional Study of Hypertension - Genelin MP; Helmkamp LJ; Steiner JF; Maertens JA; Hanratty R; Vupputuri S; Havranek EP; Dickinson LM; Blair IV; Daugherty SL (Patient Preference and Adherence, 2023)
Matthew P Genelin,1 Laura J Helmkamp,2 John F Steiner,1,3 Julie A Maertens,2 Rebecca Hanratty,1,4 Suma Vupputuri,5 Edward P Havranek,1,4,6 L Miriam Dickinson,1,2 Irene V Blair,7 Stacie L Daugherty1– 3,6 1University of Colorado School of Medicine, Aurora, CO, USA; 2Adult and Child Consortium for Outcomes Research and Delivery Sciences (ACCORDS), University of Colorado, Aurora, CO, USA; 3Institute for Health Research, Kaiser Permanente Colorado, Denver, CO, USA; 4Department of Medicine, Denver Health and Hospital Authority, Denver, CO, USA; 5Mid-Atlantic Permanente Research Institute, Kaiser Permanente Mid-Atlantic States, Rockville, MD, USA; 6Department of Medicine, Division of Cardiology, University of Colorado School of Medicine, Aurora, CO, USA; 7Department of Psychology and Neuroscience, University of Colorado Boulder, Boulder, CO, USACorrespondence: Matthew P Genelin, University of Colorado School of Medicine, 3500 Rockmont Drive, #15-209, Denver, CO, 80202, USA, Email matthew.genelin@cuanschutz.eduBackground: The strategies patients use to organize medications (eg, pill dispenser) may be reflected in adherence measured at follow-up. We studied whether medication organization strategies patients use at home are associated with adherence measured using pharmacy-fills, self-report, and pill counts.Design: Secondary analysis of data from a prospective randomized clinical trial.Setting: Eleven US safety-net and community primary care clinics.Patients: Of the 960 enrolled self-identified non-Hispanic Black and White patients prescribed antihypertensive medications, 731 patients reported pill organization strategies and were included.Variable: Patients were asked if they use any of the following medication organization strategies: finish previous refills first; use a pill dispenser; combine same prescriptions; or combine dissimilar prescriptions.Outcomes: Adherence to antihypertensive medications using pill counts (range, 0.0– 1.0% of the days covered), pharmacy-fill (proportion of days covered > 90%), and self-report (adherent/non-adherent).Results: Of the 731 participants, 38.3% were men, 51.7% were age ≥ 65, 52.9% self-identified as Black or African American. Of the strategies studied, 51.7% finished previous refills first, 46.5% used a pill dispenser, 38.2% combined same prescriptions and 6.0% combined dissimilar prescriptions. Median (IQR) pill count adherence was 0.65 (0.40– 0.87), pharmacy-fill adherence was 75.7%, and self-reported adherence was 63.2%. Those who combined same prescriptions had significantly lower measured pill count adherence than those who did not (0.56 (0.26– 0.82) vs 0.70 (0.46– 0.90), p< 0.01) with no significant difference in pharmacy-fill (78.1% vs 74%, p=0.22) or self-reported adherence (63.0% vs 63.3%, p=0.93).Conclusion: Self-reported medication organization strategies were common. Combining same prescriptions was associated with lower adherence as measured using pill counts but not pharmacy-fills or self-report. Clinicians and researchers should identify the pill organization strategies used by their patients to understand how these strategies may influence measures of patient adherence.Trial Registration: ClinicalTrials.gov NCT03028597; https://clinicaltrials.gov/ct2/show/NCT03028597 (Archived by WebCite at http://www.webcitation.org/72vcZMzAB).Keywords: hypertension, medication adherence, management strategies, organization strategies, medication management behaviors, chronic disease, pill count, pharmacy-fill, self-reported adherence